2021
DOI: 10.3390/math9151736
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Calculus in Russia at the End of XIX Century

Abstract: In this survey paper, we analyze the development of Fractional Calculus in Russia at the end of the XIX century, in particular, the results by A. V. Letnikov, N. Ya. Sonine, and P. A. Nekrasov. Some of the discussed results are either unknown or inaccessible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The differential and integral operators of arbitrary positive orders form fractional calculus [1][2][3][4][5][6][7]. The study of such operators has a long history [137][138][139][140][141][142]. Another important tool is the calculus of finite-differences of integer and non-integer orders.…”
Section: Exact Finite-difference Of Arbitrary Positive Ordermentioning
confidence: 99%
“…The differential and integral operators of arbitrary positive orders form fractional calculus [1][2][3][4][5][6][7]. The study of such operators has a long history [137][138][139][140][141][142]. Another important tool is the calculus of finite-differences of integer and non-integer orders.…”
Section: Exact Finite-difference Of Arbitrary Positive Ordermentioning
confidence: 99%
“…He observed that if f (t) = e st , t ∈ R, the summation was convergent if Re(s) > 0. This formula was the base of the fractional derivative definition used by Grünwald [60] and Letnikov [61,62]. It is important to note that the Liouville definition was assumed to be valid for functions of exponential type and defined on R or C, while Grünwald and Letnikov worked on [t 0 , t] ∈ R.…”
Section: Differences and Fractional Calculusmentioning
confidence: 99%
“…The attraction behind the development of fractional calculus is rooted in the desire to generalize the classical calculus to a wider class of functions. Fractional calculus has applications in various fields, including physics, engineering, finance, and biology [22,39]. In physics, fractional calculus is used to describe the behavior of complex systems, such as viscoelastic materials, fractals, and anomalous diffusion [13,16].…”
Section: Introductionmentioning
confidence: 99%